1997
DOI: 10.1142/s0218301397000056
|View full text |Cite
|
Sign up to set email alerts
|

Two-Pion Exchange Nuclear Potential — Chiral Cancellations

Abstract: We show that chiral symmetry is responsible for large cancellations in the two-pion exchange nucleon-nucleon interaction, which are similar to those occuring in free pion-nucleon scattering.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Nowadays, the evaluation of this part of the potential in the framework of chiral symmetry has no important ambiguities and is quite well understood. This minimal T P EP fulfills the expectations from chiral symmetry and, in particular, reproduces at the nuclear level the well known cancellations of the intermediate πN amplitude [10,11]. On the other hand, it fails to yield the qualitative features of the medium range scalarisoscalar NN attraction [8,12].…”
Section: Introductionsupporting
confidence: 59%
“…Nowadays, the evaluation of this part of the potential in the framework of chiral symmetry has no important ambiguities and is quite well understood. This minimal T P EP fulfills the expectations from chiral symmetry and, in particular, reproduces at the nuclear level the well known cancellations of the intermediate πN amplitude [10,11]. On the other hand, it fails to yield the qualitative features of the medium range scalarisoscalar NN attraction [8,12].…”
Section: Introductionsupporting
confidence: 59%
“…The fair agreement of this first calculation and data up to laboratory energies of 100 MeV or so suggests that this may become an alternative to other, more model-dependent approaches to the two-nucleon problem. Further examination of aspects of two-pion exchange in this context can be found in Celenza et al (1992), Friar and Coon (1994), da Rocha and Robilotta (1994), da Rocha and Robilotta (1995), da Rocha and Robilotta (1997), Ballot et al (1997), Savage (1997), and Kaiser et al (1997).…”
Section: Chiral Effective Theorymentioning
confidence: 99%
“…As far as dynamics is concerned, we have shown that chiral symmetry is responsible for large cancellations in the pure nucleon sector (Fig. 1, A) [16,17] and eventually the contributions from this sector turn out to be much smaller than those arising from other degrees of freedom. The main contribution to the intermediate attraction is due to processes containing nucleons in one leg and the remainder degrees of freedom in the other.…”
Section: Introductionmentioning
confidence: 91%
“…1 (A) [6][7][8][9][10]12]. These processes constitute an autonomous chiral family, incorporate correctly the well known cancellations of the intermediate πN amplitude [16,17] but correspond to an intermediate amplitude which is too simple for reproducing πN experimental data [18].…”
Section: Introductionmentioning
confidence: 99%